2020
DOI: 10.1093/mnras/staa2104
|View full text |Cite
|
Sign up to set email alerts
|

X-ray spectroscopy of the γ-ray brightest nova V906 Car (ASASSN-18fv)

Abstract: Shocks in γ-ray emitting classical novae are expected to produce bright thermal and non-thermal X-rays. We test this prediction with simultaneous NuSTAR and Fermi/LAT observations of nova V906 Car, which exhibited the brightest GeV γ-ray emission to date. The nova is detected in hard X-rays while it is still γ-ray bright, but contrary to simple theoretical expectations, the detected 3.5–78 keV emission of V906 Car is much weaker than the simultaneously observed >100 MeV emission. No non-thermal X-ray em… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 172 publications
9
36
1
Order By: Relevance
“…In V549 Vel, the quasi-simultaneous Swift and Fermi -LAT flux measurements taken on MJD 58072 result in a flux ratio of 2-77%, unambigously showing that the γray luminosity is higher. This, despite the difference in the X-ray energy ranges, is in agreement with the result of the recent Fermi -LAT and NuSTAR concurrent observations of the two novae V5855 Sgr and V906 Car, which yield ∼0.1-1% (Nelson et al 2019) and 2% (Sokolovsky et al 2020;Aydi et al 2020), respectively. However, in the nova shock model of Metzger et al (2014) with standard parameters assumed, one would expect to observe much brighter thermal X-ray emission-10 to 1000 times more luminous than the γ-ray flux-and this contradiction was also found in V5855 Sgr and V906 Car.…”
Section: Discussionsupporting
confidence: 91%
“…In V549 Vel, the quasi-simultaneous Swift and Fermi -LAT flux measurements taken on MJD 58072 result in a flux ratio of 2-77%, unambigously showing that the γray luminosity is higher. This, despite the difference in the X-ray energy ranges, is in agreement with the result of the recent Fermi -LAT and NuSTAR concurrent observations of the two novae V5855 Sgr and V906 Car, which yield ∼0.1-1% (Nelson et al 2019) and 2% (Sokolovsky et al 2020;Aydi et al 2020), respectively. However, in the nova shock model of Metzger et al (2014) with standard parameters assumed, one would expect to observe much brighter thermal X-ray emission-10 to 1000 times more luminous than the γ-ray flux-and this contradiction was also found in V5855 Sgr and V906 Car.…”
Section: Discussionsupporting
confidence: 91%
“…It was independently discovered after this by Stanek et al (2018) using the All Sky Automated Survey for SuperNovae (hereafter ASAS-SN). In this paper, we reference times as days since commencement of brightening ( 2458193 Aydi et al (2020b) suggest a value of 2 = 44 d. Sokolovsky et al (2020b) determined that this classical nova occured on a CO white dwarf, and they concluded that the mass must have been low as there was no distinct supersoft phase detected in the X-ray. Their thorough analysis of the NuSTAR, Fermi/LAT, XMM-Newton and Swift/XRT X-ray data revealed that the nova shell was expelled by +24 d. The white dwarf was found to be of CO-type by Sokolovsky et al (2020b).…”
Section: Classical Nova V906 Carmentioning
confidence: 98%
“…The mass of the white dwarf in V906 Car was estimated at 0.71 +0.23 −0.19 𝑀 through an analysis of the progenitor system by Wee et al ( 2020) using an accretion disc model to understand the light curve. Their decline times of 𝑡 2,𝑣 = 26.2 d and 𝑡 3,𝑣 = 33.0 d point to V906 Car's being a moderately fast classical nova, although Aydi et al (2020b) suggest a value of 𝑡 2 = 44 d. Sokolovsky et al (2020b) determined that this classical nova occured on a CO white dwarf, and they concluded that the mass must have been low as there was no distinct supersoft phase detected in the X-ray. Their thorough analysis of the NuSTAR, Fermi/LAT, XMM-Newton and Swift/XRT X-ray data revealed that the nova shell was expelled by +24 d. The white dwarf was found to be of CO-type by Sokolovsky et al (2020b).…”
Section: Classical Nova V906 Carmentioning
confidence: 98%